Inhibitory NPY Neurons Provide a Large and Heterotopic Commissural Projection in the Inferior Colliculus - Anair, Justin D.; Silveira, Marina A.; Mirjalili, Pooyan; Beebe, Nichole L.; Schofield, Brett R.; Roberts, Michael T. (Frontiers in Neural Circuits, 2022)
Located in the midbrain, the inferior colliculus (IC) plays an essential role in many auditory computations, including speech processing and sound localization. The right and left side of the IC are interconnected by a dense fiber tract, the commissure of the IC (CoIC), that provides each IC with one its largest sources of input (i.e., the contralateral IC). Despite its prominence, the CoIC remains poorly understood. Previous studies using anterograde and retrograde tract-tracing showed that IC commissural projections are predominately homotopic and tonotopic, targeting mirror-image locations in the same frequency region in the contralateral IC. However, it is unknown whether specific classes of neurons, particularly inhibitory neurons which constitute ~10-40% of the commissural projection, follow this pattern. We therefore examined the commissural projections of Neuropeptide Y (NPY) neurons, the first molecularly identifiable class of GABAergic neurons in the IC. Using retrograde tracing with Retrobeads in NPY-hrGFP mice of both sexes, we found that NPY neurons comprise ~11% of the commissural projection. Moreover, focal injections of Retrobeads showed that NPY neurons in the central nucleus of the IC exhibit a more divergent and heterotopic commissural projection pattern than non-NPY neurons. Thus, commissural NPY neurons are positioned to provide lateral inhibition to the contralateral IC. Through this circuit, sounds that drive activity in limited regions on one side of the IC likely suppress activity across a broader region in the contralateral IC.